2016
DOI: 10.20546/ijcrbp.2016.312.009
|View full text |Cite
|
Sign up to set email alerts
|

Further Study on Toxicity of the Permissible (Very Low) Level of Ochratoxin A with and without Essential Oils on Rats

Abstract: A feeding experiment was conducted with rats to reevaluate the possible toxic effects of very low level (tolerance limit) of ochratoxin A (OTA) and attempting to overcome this ochratoxicosis A via dietary supplementation of some essential oils. The obtained results revealed that the toxicated as well as garlic-oil groups of rats moisten their mats than the other groups' mats. Garlic-oil group also excreted more wet feces and had the lowest daily bodyweight gain as well as the worst feed conversion ratio compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Abdelhamid et al [41] in a feeding experiment with rats to reevaluate the possible toxic effects of very low level (tolerance limit) of ochratoxin A (OTA) revealed that the toxicated groups of rats moisten their mats than the other groups' mats. All toxic diets reflected high bone mineral concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Abdelhamid et al [41] in a feeding experiment with rats to reevaluate the possible toxic effects of very low level (tolerance limit) of ochratoxin A (OTA) revealed that the toxicated groups of rats moisten their mats than the other groups' mats. All toxic diets reflected high bone mineral concentration.…”
Section: Discussionmentioning
confidence: 99%